Laryngeal adenoid cystic carcinoma: case report - Negro, André Del; Ichihara, Edson; Tincani, Alfio José; Altemani, Albina; Martins, Antônio Santos (São Paulo Medical Journal, 2007)
CONTEXT: Adenoid cystic carcinomas are malignant tumors that occur in both the major and the minor salivary glands. A laryngeal location is rare because of the paucity of accessory salivary glands in this area. Adenoid cystic carcinomas account for less than 1% of all malignant tumors in the larynx, and only about 120 cases have been reported in the literature. These tumors have a slight female predisposition, and their peak incidence is in the fi fth and sixth decades of life. In this article, we describe a case of laryngeal adenoid cystic carcinoma and discuss its clinical characteristics and treatment. CASE REPORT: We report on a case of laryngeal adenoid cystic carcinoma in a 55 year-old female patient who presented with dyspnea and hoarseness. Features of the diagnostic and therapeutic evaluation are described and the clinical management of such cases is outlined. The clinical course, defi nitive treatment strategy and surgical procedure, and also adjuvant treatment with irradiation are discussed. Although the tumor is radiosensitive, it is not radiocurable.